Which part of a porcine stomach is suitable as an animal training model for gastric endoscopic submucosal dissection? - Horii, Joichiro; Goto, Osamu; Shimoda, Masayuki; Sasaki, Motoki; Fujimoto, Ai; Ochiai, Yasutoshi; Yahagi, Naohisa (Endoscopy, 2016)
Background and study aims: Training using an animal model is generally recommended before performing endoscopic submucosal dissection (ESD) in humans. This study aimed to clarify the suitability of an isolated porcine stomach as an animal training model for gastric ESD.Materials and methods: Study 1: six experienced endoscopists performed ESDs of six simulated lesions located in six locations in an isolated porcine stomach (1, lower third [L]/ greater curvature [Gre]; 2, L/ anterior wall [Ant]; 3, L/ posterior wall [Post]; 4, upper third [U]/ Gre; 5, U/Ant; 6, U/Post). The procedure times (s/cm2) were compared among the different lesion locations. A questionnaire (scored 1 – 5) completed by the endoscopists was used to assess the difference in the difficulty compared to the human stomach of the three steps of the ESD procedure (injection, incision and dissection). Study 2: the thicknesses of the mucosal layers were histologically evaluated among the six locations in three porcine and two human stomachs. Results: Study 1: the procedure speed was significantly slower at L/Gre and U/Gre in the porcine stomachs (P = 0.0004). The questionnaire responses revealed a tendency toward similarity between the lower regions of the human and porcine stomachs at L/Ant, L/Post, U/Ant and U/Post during the dissection step (P = 0.056). In contrast, the injection and incision steps at L/Gre in the porcine stomach were shown to differ in difficultly level (both P = 0.0006). Study 2: the mucosal layers in the porcine stomachs were significantly thicker than those in the human stomachs in the lower areas, especially L/Gre. Conclusions: The difficulty of ESD and the histological features of the porcine stomachs were coincident with those of the human stomachs at L/Ant, L/Post, U/Ant and U/Post. These parts of the porcine stomach may be suitable as animal training models for gastric ESD.